Differences of soil CO2 flux in two contrasting subalpine ecosystems on the eastern edge of the Qinghai-Tibetan Plateau: A four-year study. (1st February 2019) - Duan, Min; Li, Andi; Wu, Yanhong; Zhao, Zuoping; Peng, Changhui; DeLuca, Thomas H.; Sun, Shouqin
Abstract: Alpine and subalpine ecosystems on Qinghai-Tibetan Plateau are rich in soil organic carbon and are among the most sensitive regions to climate change, while little is known about the dynamics of soil carbon dioxide (CO2 ) in alpine/subalpine ecosystems except for the grassland on the plateau. In this study, the monthly and inter-annual variations in soil CO2 emission from a subalpine coniferous forest and a subalpine shrubland ecosystem on the eastern edge of the Qinghai-Tibetan Plateau were investigated from 2012 to 2015 using the opaque steady-state chamber method. Soil CO2 flux rate during the growing season ranged from 153.3 to 683.6 mg m −2 h −1 in the coniferous forest, being twice of that (76.6–347.3 mg m −2 h −1 ) in the shrubland, due to the elevation-induced differences in soil temperature and water content and the vegetation-induced differences in soil carbon and nitrogen pools. Both ecosystems showed large monthly variations in soil CO2 flux rate, while relative to the coniferous forest, the shrubland had a less inter-annual variation in soil CO2 emission. The two ecosystems had the same temperature sensitivity of soil CO2 emission, which suggests that they will respond similarly to global warming concerning soil CO2 flux rate. The results highlight the importance of soil CO2 emission in subalpine forest and shrubland ecosystems, which can be helpful to reduce the uncertainty of regional estimates of carbon budget in subalpine regions under global warming. Highlights: Soil CO2 flux rate ranged from 322.6 to 423.1 mg m −2 h −1 in the subalpine forest. Soil CO2 flux rate in the shrubland was approximately half of that in the forest. Soil temperature and water content contributed to the difference. Soil carbon and nitrogen pools also contributed to the difference. Both soils had the same temperature sensitivity of soil CO2 emission (Q10 = 3.67).